1976
DOI: 10.1083/jcb.71.3.768
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of the ultrastructural changes in rat liver induced by the peroxisome proliferator SaH 42-348.

Abstract: The changes occurring in hepatocytes of F-344 male rats during a 3-wk treatment with a hypolipidemic agent, 1-methyl-4-piperidyl-b/s[p-chlorophenoxy]acetate (Sail 42-348), have been evaluated by morphometric and biochemical methods. The twofold increase in liver weight resulted from a significant increase in hepatocyte cytoplasm as well as a moderate increase in the number of liver cells. The peroxisome population and SER played an overwhelming part in the hypertrophy of hepatocytic cytoplasm. The relative vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
0
3

Year Published

1978
1978
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(70 citation statements)
references
References 35 publications
8
59
0
3
Order By: Relevance
“…Proliferation of microbodies due to the effect of several hypolipidemic agents has been examined by biochemical assay of catalase (7), by electron microscopic cytochemistry (24) and more recently by morphometric analysis (18,29).…”
Section: Discussionmentioning
confidence: 99%
“…Proliferation of microbodies due to the effect of several hypolipidemic agents has been examined by biochemical assay of catalase (7), by electron microscopic cytochemistry (24) and more recently by morphometric analysis (18,29).…”
Section: Discussionmentioning
confidence: 99%
“…Bout et al (1990) also reported that transcripts for 3-oxoacyl-CoA thiolase, another enzyme of the lipid 0-oxidation pathway, were increased in centrilobular hepatocytes. Because the proliferation of peroxisomes as determined by morphometry (Moody and Reddy, 1976) and the concentration of PH protein as revealed by quantitative immunogold labeling are also more pronounced in the same region of the liver lobule (Lindauer et al, 1994), it is likely that pericentral hepatocytes respond more vigorously to peroxisome-proliferating agents. Recently, several nuclear receptors, called peroxisome proliferator-activated receptors (PPARs), have been identified and were shown in transactivation assays to induce the transcription of peroxisomal &oxidation enzyme genes (Wahli et al, 1995;Green and Wahli, 1994).…”
Section: Hepatic Zonal Heterogeneity Of the Induction Of Mrnas Encodimentioning
confidence: 99%
“…Whereas the increased transcription of genes encoding the p-oxidation enzymes has been well documented by Northern blotting (Nemali et al, 1988;Reddy et al, 1986), little is known about the exact spatial distribution of corresponding "As in the liver lobule. The proliferation of peroxisomes, however, is quite heterogeneous, with many compounds being more pronounced in pericentral (Zone 3) region of the liver lobule (Gorgas and Krisans, 1989;Baumgart et al, 1987;Moody and Reddy, 1976). Using immunoelectron microscopy with protein A-gold and quantitative image analysis, we recently showed that the elevation of individual P-oxidation enzymes varies in different parts of the liver lobule, depending on the type of xenobiotic compound used (Lindauer et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…All the above effects of hypolipidemic drugs were fully reversed after withdrawal of the drugs. After cessation of the drugs, cellular peroxisome levels decreased to the control level within 1 week (9,27). To investigate the peroxisome degradation process, the decrease in proliferated peroxisomes was measured after withdrawal of the drugs.…”
Section: Autophagic Degradation Of Peroxisomes Induced By Hypolipidemmentioning
confidence: 99%
“…Moody and Reddy reported that they administered the clofibrate derivative 1-methyl-4-piperidyl-bis[p-chlorophenoxy] acetate (SaH 42-348) to rats by mixing the reagent with chow at a concentration of 0.10% (wt/wt) for 3 weeks. By the treatment, the liver weight and the relative volume of peroxisomes increased 2-and 8.4-fold, respectively (9).…”
mentioning
confidence: 99%